Foreign political connections - Sojli, Elvira; Tham, Wing Wah (Journal of International Business Studies, 2017)
Liability of foreignness, a firm’s social and economic costs of operating in a foreign market, is a major concern for multinational corporations and firms trying to enter new markets. To reduce the liability of foreignness, a firm may engage in strategic international political management via foreign political connections and thus lower barriers to entry. Faccio (Am Econ Rev 96(1):369–386, 2006) suggests that political connections can be established by having large shareholders, who are politicians or are politically connected. This paper investigates the value of such foreign political connections for publicly listed firms. We find that foreign political connections create large firm value and improve access to foreign markets. One of the main channels of value creation is government contracts awarded to firms with direct foreign political connections. Our findings provide evidence of the effectiveness of having large and active foreign politically connected shareholders as part of a firm’s international political corporate strategy.